Neonatal Surgical Situation in Bangladesh: Challenges and Way Forward (Journal of Paediatric Surgeons of Bangladesh, 2025)
The neonatal period is the most vulnerable time for a child. Although neonatal morbidity and mortality have declined over the last few decades, the outcome of neonatal surgery is still relatively poor in Bangladesh compared to other low- and middle-income countries. Still, neonatal surgery is not getting its due attention in the national health policy. Here, challenges are multifactorial. In developed countries, intrauterine diagnosis, planned delivery, better pediatric anesthetic support, improved neonatal intensive care, and prompt surgical management have been shown to significantly improve neonatal surgical outcomes. This article addresses various problems of delivering neonatal surgical services in Bangladesh and proposes solutions. It is crucial that prompt surgical management be a key focus in improving neonatal and infant health indices.Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):24-32